2014
DOI: 10.3109/10903127.2013.851309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Success Rates between Two Video Laryngoscope Systems Used in a Prehospital Clinical Trial

Abstract: The CMAC had a higher likelihood of successful intubation compared to the King Vision. Complication rates were not statistically different between groups. Video laryngoscope placement success rates were not higher than our historical direct laryngoscopy success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…The technique used with nondisplacing devices may be more foreign to experienced operators, require a different skill set, and contribute to the rapid drop-off seen in the Burnett et al paper. 19 We determined that we had to train our medics to consider intubating with the nondisplacing King Vision, to be a different skill than using DL. We instructed the paramedics to hold the device low down on the blade (Figure 3) rather than using the handle itself (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique used with nondisplacing devices may be more foreign to experienced operators, require a different skill set, and contribute to the rapid drop-off seen in the Burnett et al paper. 19 We determined that we had to train our medics to consider intubating with the nondisplacing King Vision, to be a different skill than using DL. We instructed the paramedics to hold the device low down on the blade (Figure 3) rather than using the handle itself (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It has a hyperacute, angled blade, similar to the GlideScope (Verathon Medical, Bothell, WA) device, which uses an indirect, nondisplacing intubating technique. Recently, several studies have evaluated its use, compared both with DL and with other VL devices, [16][17][18][19] again with mixed results. We identified poor intubation success using DL (64.9% overall success) during normal quality improvement efforts at a suburban EMS system.…”
Section: Introductionmentioning
confidence: 97%
“…A 2009 study comparing overall success rates for the GlideScope and C‐MAC video devices (both devices represented in this meta‐analysis) on simulated manikin airways found that the C‐MAC device was superior . In addition, a study by Burnett et al . showed that the C‐MAC device outperformed the King Vision device in both first‐pass success and overall success rates in a nonrandomized, controlled trial.…”
Section: Limitationsmentioning
confidence: 99%
“…as good as and may be situationally more effective than DL under unusual circumstances such as, entrapped patients with both normal and difficult airways [10,20,21]. Other potential uses and future studies include unexpected in-hospital code situations on ward beds, international travel emergencies, public arenas, disaster scenarios, and pre-hospital intubation.…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%